Metagenomic 16S rDNA Illumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities. (18th September 2013) - Logares, Ramiro; Sunagawa, Shinichi; Salazar, Guillem; Cornejo‐Castillo, Francisco M.; Ferrera, Isabel; Sarmento, Hugo; Hingamp, Pascal; Ogata, Hiroyuki; de Vargas, Colomban; Lima‐Mendez, Gipsi; Raes, Jeroen; Poulain, Julie; et al.
Summary Sequencing of 16S rDNA polymerase chain reaction (PCR) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR. Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes (mitags) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the Tara Oceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for Roche‐454 sequencing using both shotgun (m454tags; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon (454tags; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mitags may provide more realistic estimates of community richness and evenness than amplicon 454tags. In addition, mitags can capture expected beta diversity patterns. Using mitags is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic (Bacteria, Archaea and Eukarya) and functional information from the same microbial community.